The Association between Vitamin D 25(OH)D Level andAlbuminuria in Type 2 Diabetes Mellitus - Indra, Tities Anggraeni; Lydia, Aida; Purnamasari, Dyah; Setiati, Siti (UI Scholars Hub, 2017)
Introduction. Vitamin D 25(OH)D deficiency was reported as a possible risk factor for the development of diabetic nephropathy in several epidemiologic studies. Whether vitamin D 25(OH)D deficiency plays a role in the development of diabetic nephropathy in Indonesia is unknown. This study aims to determinate the association between vitamin D 25(OH)D level with albuminuria in patients with type 2 diabetes mellitus in Indonesia. Methods. A cross-sectional study was conducted in 96 patients with type 2 diabetes mellitus at outpatient clinic of MetabolicEndocrine Cipto Mangunkusumo Hospital. Serum vitamin D level was assessed using Diasorin kit with CLIA method, while albuminuria was assessed using random urine sample. Statistical analysis was conducted using chi square for bivariate analysis and regression logistic method for multivariate analysis. Results.The prevalence of vitamin D 25(OH)D deficiency in patients with type 2 diabetes mellitus was 49% with a median value 16,35 (4,2-41,4) ng/mL. There was no significant correlation between vitamin D deficiency with the severity of albuminuria (OR 0,887; 95% CI 0,335 to 2,296). Confounding factors such as poor blood glucose control and overweight strongly influenced the association between vitamin D deficiency with the incidence of albuminuria in patients with type 2 diabetes mellitus. Conclusion. The results of this study showed that there was no association between vitamin D deficiency with the severity of albuminuria in patients with type 2 diabetes mellitus in Indonesia.